2002
DOI: 10.1348/00070990260377596
|View full text |Cite
|
Sign up to set email alerts
|

Relaxed conditions can provide memory cues in both undergraduates and primary school children

Abstract: For both primary school children and university students, the educational implication of these findings is that learning can be improved in a relaxed state. For this benefit to be fully manifest, the assessment of learning should also take place under relaxed conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
1
11
0
2
Order By: Relevance
“…Students also commented that the flipped approach allowed for a more relaxed environment for them to learn. This is in keeping with work by Cassady et al who noted that a relaxed learning environment can help to provide effective retrieval cues and improve learning (Cassaday, Bloomfield, & Hayward, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Students also commented that the flipped approach allowed for a more relaxed environment for them to learn. This is in keeping with work by Cassady et al who noted that a relaxed learning environment can help to provide effective retrieval cues and improve learning (Cassaday, Bloomfield, & Hayward, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Individual items indicated that most often students expected that the atmosphere would be relaxed (M=3.99; SD=0.77) and comfortable (M=3.76; SD=0.77) during the lessons, and that embattled students would get help (M=3.70; SD=0.92). Although simulation exercises sometimes cause nervousness (Alinier, Hunt, Gordon & Harwood, 2006;Cleave-Hogg & Morgan, 2002), students in this study expected the atmosphere to be relaxed during the lessons, which is a prerequisite for good learning (e.g., Cassaday, Bloomfield & Hayward, 2002). In simulation-based training, it is important that students be allowed to make mistakes without being ridiculed or humiliated.…”
Section: Students' Expectations Of Their Academic Self-perception Andmentioning
confidence: 90%
“…That is, they require the learner to change his or her approach to learning. Some of the strategies include studying in groups (Johnson & Johnson, 1983;Nastasi & Clements, 1991), active learning (e.g., Cherney, 2008), focusing on key words (Reutzel & Hollingsworth, 1988), using specific note-taking and review strategies that emphasize the encoding specificity principle (Kobayashi, 2006), maintaining congruence of encoding and retrieval conditions (Cassaday, Bloomfield, & Hayward, 2002;Metzger, Boschee, Haugen, & Schnobrich, 1979), and employing imagination (Cooper, Tindall-Ford, Chandler, & Sweller, 2001;Leahy & Sweller, 2005) or mnemonics Carney & Levin, 2002;Dretzke, 1993;Levin & Levin, 1990;Peters & Levin, 1986;Rummel, Levin, & Woodward, 2003). Yet, some strategies are better than others (Butler & Roediger, 2007;Rickards & McCormick, 1988) and each strategy has limitations.…”
Section: Introductionmentioning
confidence: 99%